Overexpression of alanine-glyoxylate aminotransferase 2 protects from asymmetric dimethylarginine-induced endothelial dysfunction and aortic remodeling - Rodionov, Roman N.; Jarzebska, Natalia; Burdin, Dmitrii; Todorov, Vladimir; Martens-Lobenhoffer, Jens; Hofmann, Anja; Kolouschek, Anne; Cordasic, Nada; Jacobi, Johannes; Rubets, Elena; Morawietz, Henning; O'Sullivan, John; et al. (Scientific Reports, 2022)
Elevated plasma concentrations of asymmetric dimethylarginine (ADMA) are associated with an increased risk of mortality and adverse cardiovascular outcomes. ADMA can be metabolized by dimethylarginine dimethylaminohydrolases (DDAHs) and by alanine-glyoxylate aminotransferase 2 (AGXT2). Deletion of DDAH1 in mice leads to elevation of ADMA in plasma and increase in blood pressure, while overexpression of human DDAH1 is associated with a lower plasma ADMA concentration and protective cardiovascular effects. The possible role of alternative metabolism of ADMA by AGXT2 remains to be elucidated. The goal of the current study was to test the hypothesis that transgenic overexpression of AGXT2 leads to lowering of plasma levels of ADMA and protection from vascular damage in the setting of DDAH1 deficiency. We generated transgenic mice (TG) with ubiquitous overexpression of AGXT2. qPCR and Western Blot confirmed the expression of the transgene. Systemic ADMA levels were decreased by 15% in TG mice. In comparison with wild type animals plasma levels of asymmetric dimethylguanidino valeric acid (ADGV), the AGXT2 associated metabolite of ADMA, were six times higher. We crossed AGXT2 TG mice with DDAH1 knockout mice and observed that upregulation of AGXT2 lowers plasma ADMA and pulse pressure and protects the mice from endothelial dysfunction and adverse aortic remodeling. Upregulation of AGXT2 led to lowering of ADMA levels and protection from ADMA-induced vascular damage in the setting of DDAH1 deficiency. This is especially important, because all the efforts to develop pharmacological ADMA-lowering interventions by means of upregulation of DDAHs have been unsuccessful.
CRIS-Team WoS Importer:2022-07-01